The inheritance of loss - Desai, Kiran, 1971- (New York : Grove Press ; [Berkeley, Calif.] : Distributed by Publishers Group West, 2006)
In a crumbling house in the remote northeastern Himalayas, an embittered, elderly judge finds his peaceful retirement turned upside down by the arrival of his orphaned granddaughter, Sai.
Originally published: New York : Atlantic Monthly Press, 2006.
"Reading group guide inside"--P. [4] of cover.